Előléptetések
Jenő Vladár, Béla Elefánti, József Matta, Vilmos Horvay, Antal Stempel, Jakab Font, István Klinczkó, Béla Farkas, István Lovassy, Gábor Szikszay, Domonkos Malinay, Lajos Fabián, Dr. Vilmos Kemény a Ferenc Okolicsányi z 9. honvédskeho pešieho pluku boli povýšení na poručíkov.